WARP: A Unique Extracellular Matrix Component of Cartilage, Muscle, and Endothelial Cell Basement Membranes. Issue 6 (5th March 2019) - Fitzgerald, Jamie
ABSTRACT: The von Willebrand factor A‐domain‐related protein (WARP) encoded by the VWA1 gene, is an orphan extracellular matrix protein that is expressed in a subset of ECM structures but whose function is poorly understood. Here, recent advances on understanding VWA1/WARP will be reviewed including analysis of VWA1 reporter and global knock‐out mice, interaction studies, and recent transcriptome analyses. Anat Rec, 2019. © 2019 Wiley Periodicals, Inc.